2016
DOI: 10.4274/jcrpe.2824
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone Methyl Oxidase Deficiency Type 1 with Normokalemia in an Infant

Abstract: Isolated aldosterone synthase deficiency may result in life-threatening salt-wasting and failure to thrive. The condition involves hyperkalemia accompanying hyponatremia. Two types of aldosterone synthase deficiency may be observed depending on hormone levels: corticosterone methyl oxidase type 1 (CMO 1) and CMO 2. Herein, we describe a Turkish infant patient with aldosterone synthase deficiency who presented with failure to thrive and salt wasting but with normal potassium levels. Urinary steroid characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
3
5
1
Order By: Relevance
“…Previously, only 2 genetically confirmed Turkish patients were reported in two different articles (p.G435S and p.I263N mutations). 15,20 In this study, both patients 1 and 2 are homozygous for p.I263N, the same variant reported by Ustyol et al 20 There has not been a reported functional study of this variant. Nevertheless, with the addition of these 2 unrelated patients, it is clear that the isoleucine-to-asparagine substitution at codon 263 in CYP11B2 is disease causing.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Previously, only 2 genetically confirmed Turkish patients were reported in two different articles (p.G435S and p.I263N mutations). 15,20 In this study, both patients 1 and 2 are homozygous for p.I263N, the same variant reported by Ustyol et al 20 There has not been a reported functional study of this variant. Nevertheless, with the addition of these 2 unrelated patients, it is clear that the isoleucine-to-asparagine substitution at codon 263 in CYP11B2 is disease causing.…”
Section: Discussionsupporting
confidence: 80%
“…Three of the IHA patients in this study whose initial endocrinological evaluation showed hyperreninaemic hypoaldosteronism had been successfully treated with fludrocortisone. Previously, only 2 genetically confirmed Turkish patients were reported in two different articles (p.G435S and p.I263N mutations) . In this study, both patients 1 and 2 are homozygous for p.I263N, the same variant reported by Ustyol et al .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Typically, the disease manifests in the first weeks of life with nausea, vomiting, feeding problems and failure to thrive in the neonatal period. Isolated aldosterone deficiency is associated with neonatal salt-wasting syndrome resulting in hyponatremia, hyperkalaemia, metabolic acidosis and marked elevated renin with low or unappropriated normal aldosterone levels (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Usually, clinical severity improves with age and patients are frequently asymptomatic during adulthood despite not having mineralocorticoid therapy (16).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the cases reported in the literature are from Iranian Jewish patients (5,16,17), but cases from Turkey (14,18) , Japan (7,8) and Israel (9,19) have also been described. To our knowledge, there has been no previous report of Portuguese cases of AS deficiency, especially with confirmed genetic analysis.…”
Section: Introductionmentioning
confidence: 99%